A comparative study of source specific multicast and aggregated source specific multicast - Ahmad, Taqiyuddi; Zainal Arifin, Muaz; Hassan Abdalla Hashim, Aisha; Anwar, Farhat; Al-Irhayim, Sufyan (Faculty of Engineering, International Islamic University Malaysia, 2008)
Source Specific Multicast (SSM) has been introduced to overcome the issues in Any Source Multicast (ASM) such as security, deployment complexity and address allocation. However, the scalability issue of SSM still poses a problem. To solve this state scalability problem, a scheme called aggregated multicast is proposed. The key idea is that multiple groups are forced to share a single delivery tree. In this paper, the basic idea of SSM and ASSM is give and a comparison between both is done. Based on what we have done, we conclude that aggregated multicast is an effective way to solve the scalability issue of SSM. However, it may suffer from routers under utilization problem. To achieve higher routers utilization, this paper proposes a new approach. The new approach was also discussed.